Production Of High-Alumina Slags In The Blast Furnace - T. L. Joseph (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
IN connection with its investigations of the blast'-furnace process, the Bureau of Mines, in coöperation with the Minnesota School of Mines Experiment Station, developed a 6-ton experimental furnace. Such a furnace was needed to determine the feasibility of producing ferromanganese from Minnesota manganiferous iron ores, a problem of national importance because of the present need for manganese in the steel industry and our small reserves of ferro-grade ores. Furnace operators are reluctant to use new or untried raw materials or to make decided innovations in practice on account of the financial hazard of experimenting with full-scale equipment. A small furnace which can be operated at a relatively low cost is particularly adapted for testing new, raw materials and for determining the feasibility of decided innovations in practice. Laboratory experiments, plus whatever information may be available, are valuable but often do not indicate the net result of changes in an operation involving a large number of interrelated variables. From time to time the coöperation of the Bureau of Mines is solicited in connection with problems involving departures from normal procedure. Under these circumstances some sort of a practical demonstration is a desirable forerunner to full-scale operations which appear feasible after small-scale tests.